HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN PEMERIKSAAN ANTENATAL CARE DI KELURAHAN LAING WILAYAH KERJA PUSKESMAS NAN BALIMO KOTA SOLOK - Afridon Afridon (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Antenatal care examination is an examination of pregnancy to optimize the mental and physical health of pregnant women, so that they are able to face childbirth, when the childbirth, preparation for breastfeeding and the return of reproductive health properly. Factors that can influence the behavior of pregnant women in making K1 and K4 visits include maternal knowledge, attitudes and actions. The design of this study correlated with the cross sectional approach, namely in this study which became the independent variable of knowledge and attitude and the dependent variable of antenatal care examination. The results of the analysis between knowledge and antenatal care found that most (92.3%) respondents had low knowledge of irregularity in antenatal care. While the statistical test obtained p value 0.001 ˂ 0.05 which means that there is a significant relationship between the level of low knowledge and irregularity in conducting pregnancy examinations, the results of the analysis of attitudes with antenatal care were found to be more than a portion (77.8%) of respondents who had attitudes negative irregularity in antenatal care. While the statistical test obtained p value 0.014 ˂ 0.05, which means there is a significant relationship between negative attitudes with irregular pregnancy checks. It is expected that health workers can be able to provide knowledge to pregnant women about the importance of regular pregnancy checks that will benefit mothers and their babies to improve health and prevent premature babies and prevent risks to mothers during childbirth.